Anthropometric and physiological characteristics of 13-14-year-old female volleyball players in different playing positions - Cherouveim, E.; Tsolakis, C.; Ntozis, C.; Apostolidis, N.; Gkountas, K.; Koulouvaris, P. (Journal of Physical Education and Sport, 2020)
Introduction: Despite the differentiation of anthropometric and physiological demands according to the technical and tactical requirements of each playing positionin adults, only few studies have examined this issue in young female volleyball players. Thus, the aim of this study was to investigate the effects of playing positions and age on anthropometric characteristics and exercise performance in young female volleyball players. Material and Methods: A total of 389 healthy females (n = 389, 14.2 ± 5.5 years old, body mass of 57.05 ± 9.48 kg, height of 1.67 ± 0.07 m, and body mass index of 20.28 ± 2.76), who are high-level volleyball players, volunteered to participate in this study. Participants were divided into six groups according to their playing position [i.e., setters (n = 66), outside-hitters (n = 125), middle blockers (n = 66), opposites (n = 37), liberos (n = 25), and without a specific position (n = 70)] and into two age groups [i.e., 13 (AG13, n = 127) and 14 (AG14, n = 262) years old]. All athletes were assessed for anthropometric characteristics and physical performance. Specifically, athletes completed overhead medicine ball throw (MBT), standing long jump (LJ), countermovement jump (CMJ), spike jump (SJ), flexibility, agility T-test, and sit-ups (SU) trials. Results:There was a significant difference (p < 0.05) among playing positions in terms of anthropometrics and exercise performance. Specifically, volleyball players without a specific playing position had a smaller body morphology and lower exercise performance (in MBT, LJ, CMJ, SJ, SRT, AT, and UP) compared to other playing positions. However, physiological characteristics were similar (p>0.05) among volleyball players with specific playing positions. Regarding age, there was a significant effect on exercise performance, and the mean values of LJ, CMJ, SPJ, MBT, and agility test were higher in olderathletes than in younger ones; whereas sit-ups values were higher in younger players than in older ones. Significant correlations were observed between jumping ability and anthropometric characteristics. Conclusion: The results of this study can be used as reference values duringthe talent selection process to provide specific playing position data for this age-group category.The lack of physiological differences among playing positions confirms that anthropometric characteristics can be an adequate identification factor for the primary talent selection for this age group.